The influence of apolipoprotein A5 T-1131C and apolipoprotein E common genetic variants on the levels of hemostatic markers in dyslipidemic patients - Novotny, Dalibor; Karasek, David; Vaverkova, Helena; Slavik, Ludek (Clinica chimica acta, 2014)
OBJECTIVES: The aim of this study was to evaluate the relationships of the T-1131C (rs662799) polymorphism variants of apolipoprotein A5 (Apo A5) gene and variants of apolipoprotein E (Apo E) gene common polymorphism (rs429358, rs7412) to selected hemostatic markers. STUDY DESIGN AND METHODS: We examined 590 asymptomatic dyslipidemic patients, subsequently divided into MetS+ (n=146) and MetS- (n=444) groups according to the criteria for identification of the metabolic syndrome (MetS). We compared variant frequencies and differences in levels of hemostatic markers according to Apo A5, Apo E and Apo A5/Apo E common variants. RESULTS: The -1131C Apo A5 minor variant was associated with elevated tissue plasminogen activator (tPA) in comparison to TT genotype (p<0.001), but not in the MetS+ group. The analysis of Apo A5/Apo E common variants in all subjects revealed that the presence of -1131C minor allele has always been associated with higher levels of tPA in comparison with T allele, regardless of Apo E genotype. Also the presence of minor Apo E2 allele led to elevated tPA concentrations in both T and C carriers. In addition, common -1131C/E2 variant was associated with the highest tPA levels. CONCLUSION: We demonstrated a remarkable association especially between the -1131C Apo A5 variant and increased tPA levels in asymptomatic dyslipidemic patients.
Keywords: dospělí; apolipoproteiny E; Hemostasis; apolipoproteiny A; Female; Tissue Plasminogen Activator; biologické markery; Biomarkers; Dyslipidemias; Adult; asymptomatické nemoci; ženské pohlaví; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; hemostáza; Male; Apolipoproteins E; dyslipidemie; lidé středního věku; Asymptomatic Diseases; tkáňový aktivátor plazminogenu; mužské pohlaví; Apolipoproteins A; Middle Aged; Humans